1999
DOI: 10.1111/j.1572-0241.1999.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Angiogenic Factors in Human Colonic Angiodysplasia

Abstract: In human colonic angiodysplasia, increased expression of angiogenic factors is likely to play a pathogenic role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 27 publications
2
65
1
1
Order By: Relevance
“…Recent studies have suggested that angiogenesis is involved in the pathogenesis of vascular malformations. 21 Increased VEGF expression has been reported in human colonic angiodysplasia 22 and, more recently, anti-angiogenic treatments have been cautiously tested to control bleeding from vascular malformations, with promising results (reviewed by Bauditz and Lochs 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that angiogenesis is involved in the pathogenesis of vascular malformations. 21 Increased VEGF expression has been reported in human colonic angiodysplasia 22 and, more recently, anti-angiogenic treatments have been cautiously tested to control bleeding from vascular malformations, with promising results (reviewed by Bauditz and Lochs 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that angiogenesis is involved in the pathogenesis of vascular malformations. 21 Increased VEGF expression has been reported in human colonic angiodysplasia 22 and, more recently, anti-angiogenic treatments have been cautiously tested to control bleeding from vascular malformations, with promising results (reviewed by Bauditz and Lochs 23 ).Because of its relationship with regulators of angiogenesis and the clinical observations of angiodysplasia in VWD patients, we postulated that VWF may regulate angiogenesis. Using human umbilical vein ECs (HUVECs), we found that inhibition of VWF expression by short interfering RNA (siRNA) in vitro resulted in increased stability of the capillary network in a 3D tube-formation assay, increased VEGFR-2-dependent proliferation and migration, which was coupled to a decrease in ␣v␤3 levels and activity and increased Ang-2 release.…”
mentioning
confidence: 97%
“…VEGF, so far the best characterized angiogenic molecule, stimulates proliferation of vascular endothelial cells and increases vascular permeability, and thus is a central mediator of the early phase of angiogenesis [10] . Recent studies have confirmed that both Osler's disease and nonhereditary intestinal angiodysplasias are characterized by increased production of VEGF [11,12] . High serum levels of VEGF that also correlate with severity of bleeding are found in patients with Osler's disease [11] .…”
Section: Mechanisms Of Bleedingmentioning
confidence: 85%
“…Expression of VEGF receptor 1 is also observed in bleeding intestinal angiodysplasias [12] . As VEGF receptor 1 is specifically up-regulated by hypoxia, this finding may indicate a role for hypoxia in the pathogenesis of angiodysplasias [13,14] .…”
Section: Mechanisms Of Bleedingmentioning
confidence: 92%
See 1 more Smart Citation